Validation of the MIMOSA-AURORA-IFDM model chain for policy support: Modeling concentrations of elemental carbon in Flanders - Lefebvre, Wouter; Vercauteren, Jordy; Schrooten, Liesbeth; Janssen, Stijn; Degraeuwe, Bart; Maenhaut, Willy; de Vlieger, Ina; Vankerkom, Jean; Cosemans, Guido; Mensink, Clemens; Veldeman, Nele; Deutsch, Felix; et al. (Atmospheric environment (1994), 2011)
The ability of a complex model chain to simulate elemental carbon (EC) concentrations was examined. The results of the model chain were compared to EC concentration measurements made at several locations, every sixth day. Two measurement campaigns were taken into account, one in 2006–2007 and one in 2008–2009. The model results compare very well for both periods, with an R 2 of 0.74, a bias of 0.02 μg m −3 and a RMSE of 0.32 μg m −3. Sensitivity analyses to different meteorology inputs and changing emissions from year to year were performed. The differences between the two measurement periods were also investigated. It is shown that somewhat more than half of these differences is due to meteorology. However, emission changes also play an important role. ► The ability of a model chain to simulate elemental carbon was examined. ► The model simulations were made at very high resolutions. ► The results of the model chain were compared to EC concentration measurements. ► The model results compare very well for both periods: R 2 = 0.74; Bias = 0.02 μg m −3. ► Sensitivity analyses to different meteorology inputs and changing emissions.